Rethinking study abroad: post-pandemic perspectives on international exchange in Japan - Chika Yamamoto Rosenbaum; Nami Iwaki; Yoko Tatsumi (Cogent Education)
As a result of the COVID-19 pandemic, significant scholarly attention has been given to whether virtual study abroad can replace traditional study abroad. By contrast, the question of whether domestic activities involving interaction with foreign students, known as intercultural exchange, can be an alternative in the post-pandemic era has received much less empirical attention. This study addresses this gap by analyzing factors influencing the interests of over 600 Japanese students in both traditional study abroad and intercultural exchange. Our ordered logit analysis suggests that intercultural exchange can serve as an attractive substitute for traditional study abroad, given the following findings. First, several of the same factors affect students’ interest in both activities. Second, and perhaps more importantly, barriers to studying abroad significantly boost students’ interest in intercultural exchange but not in study abroad. In other words, when students are concerned about going abroad, they turn to intercultural exchange, which is relatively easy to participate in. Ultimately, these findings underscore the value of universities focusing on quality global experiences within home countries in the post-pandemic era.